Implementasi Metode Marr-Hilldert Untuk Mendeteksi Batas Wilayah Gempa - Rajagukguk, Lanna (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2022)
he development of technology is currently increasing significantly and has become a dependent tool for humans around the world because the role of technology can help solve problems that are difficult for humans to solve. One form of positive role from technological developments is to detect the edges of digital images. Indonesia is one of the countries with the highest potential for earthquakes in the world, the cause of Indonesia is earthquake prone because it has many volcanoes not only from the Pacific Ring of Fire. There is still the Alpide Belt which is the most active earthquake pathway in the world, which is also influenced by the occurrence of earthquakes in Indonesia. In addition, there are also piles of three continental plates, namely the Indonesia-Australia plate from the south, Eurasia from the north, and the Pacific plate from the east which adds to the hustle and bustle of the geological structure in this country. Therefore, the need for information but detecting the boundaries of the earthquake area is very much needed to be able to minimize the negative impacts that occur, especially casualties, so far this information is still lacking